Implementation of Hadith on the Influence of Parenting Style on Child Development : Implementasi Hadis tentang Pengaruh Gaya Parenting Orang Tua terhadap Perkembangan Anak - Nurul Inayah, Nadia; Agung Danarta; Muhammad Alif (Jurnal Living Hadis, 2024)
The parent's role in the legal action of building children's character is to encounter new situations along with modern times. Various new challenges are undeniable, such as social, cultural, and economic issues, and the increasingly massive development of digital technology. It should affect the parenting process, where parents are required to observe and control everything that their children do. This study was conducted to find out the hadith commentary on the concept of "parenting", by understanding how children learn and the role of parents in being responsible for their children's education. Hadiths are relevant to parenting learning through two problems. First, what are the characteristics of educators from the perspective of hadith? Second, what are the methods taught by the Prophet in educating children? To answer the two problems, the author used a literature study based on the grounded theory of Saldaña and Anselm Strauss and made the concept of contemporary learning parenting a sensitizing concept. The results show that there are at least 12 hadiths that are relevant to the idea of parenting and produce four characteristics of educators that should be applied in the parenting process, as well as three methods that parents can use in the parenting process. It is important to support the success of every parent in educating, directing, and making children a person with positive character.